International scientific conference Russian-Mongolian relations: from origins to modernity - S. A. Semedov; B. Javzandolgor (Концепт: философия, религия, культура, 2021)
International scientific conference Russian-Mongolian Relations: from Origins to Modernity dedicated to the 100th anniversary of the establishment of diplomatic relations between Russia and Mongolia took place on February 19, 2021. More than 200 scientists, researchers, and enthusiasts from 15 countries gathered in Moscow to discuss a wide range of questions concerning the historical and present state of diplomatic, business, and cultural Russian-Mongolian relations. Iskander Aziziv and Dulamsürengiin Davaa, Extraordinary and Plenipotential Ambassadors of the countries, opened the conference and shared their optimism on the future development of international relations between Russia and Mongolia. The participants presented their ideas and research results on the strategic and humanitarian cooperation between the countries and emphasized the traditional understanding of the partnership that had formed between these different civilizations. It was important to talk about the need for mutual understanding for the cause of world peace. The conference served as a platform for establishing academic and research relations. Russian specialists on international education presented their view on the educational partnership between the countries, including China, in the globalizing world with a clear western leaning. Participants suggested measures to reverse the decline of Russian language learning among younger students in Mongolia. Leading Mongolian scientists spoke on the particular aspects of Russian-Mongolian bilateral relations. J. Battogtokh underlined that the State of Mongolia signed its very first international treaty with Russia and since then the countries respected the legality of their agreements both long-standing and newly concluded. The resolution inspired optimism: Russia and Mongolia have a solid legal foundation for developing their relations and a growing number of established ties inspire optimism. The cultural and political section of the conference featured reports by researchers from various countries. In these reports, historical aspects of the times of the Golden Horde, traditional Mongolian values, and the specificity of Mongolian relations with Turkish nations and neighboring China were covered. As it was noted, Mongolia managed to conserve its identity and independent national politics in all the diverse relations it has been engaged in. The conference attracted numerous experts, students, and practitioners and provided a great opportunity for the specialists to share their knowledge with a wider audience and to promote Russian-Mongolian relations to benefit both nations and the global community.